The impact of gender and risk factors for hearing impairment on audiogram changes in military cadets during shooting exercises - Jovanović, Vanja; Vojvodić, Danilo; Jovanović, Dejan; Marjanović, Sonja (Vojnosanitetski pregled, 2025)
Background/Aim. Military personnel are frequently exposed to high levels of noise, where hearing loss can affect their combat performance. The aim of this study was to assess the impact of impulse noise produced by firearms during shooting exercises, analyze the effect of noise through pure-tone audiometry, and correlate it with sex differences and risk factors for hearing impairment. Methods. The study included 105 cadets, 75 men and 30 women, aged 19 to 25 years, who underwent regular firearm shooting as part of their military training. We observed the results of audiometric examinations conducted at three time points: 24 hrs before noise exposure, immediately after the noise exposure [shooting with a “Crvena Zastava” 99 pistol, i.e., CZ99], and 24 hrs after the shooting. Data on risk factors were obtained from a questionnaire with anamnestic data of the cadets. Results. Immediately after noise exposure, there was significant sensorineural hearing impairment at 2,000 Hz and 4,000 Hz, with complete recovery after 24 hrs. Our study revealed that male participants are more susceptible to this type of noise exposure compared to female participants. Additionally, we found that 22.9% of the respondents had risk factors for post-shooting hearing impairment, which included smoking, noise exposure within the last 7 days, field work within the past 72 hrs, and hereditary hearing loss in the family. Conclusion. Despite the regular use of hearing protection, hearing impairment after acute acoustic trauma caused by shooting in military personnel remains inevitable and is more pronounced in men than in women. Our results suggest that the presence of risk factors for hearing impairment contributes to an increase in the temporary threshold shift, i.e., a decrease in hearing.
Keywords: audiometry; hearing loss; hearing loss, noise-induced; military medicine; risk factors; sex factors.